The influence of fruit and vegetable mixtures on the organoleptic properties of sorbets - E. N. Efremova; O. A. Sutorma; D. D. Khoroshilov; K. A. Ambrosova (Новые технологии, 2024)
Currently, the quality of school meals plays important role for the parents of schoolchildren. Expanding the range of food with hypoallergenic products is an urgent problem. In our research sorbet was used as a research object. Fruit and vegetable crops were used as the basis for the sorbet prototype. Zucchini, green apple and white currant were selected as the main ingredients of sorbets, taking into account the recommendations of a non-specific hypoallergenic diet. The goal of the research was to develop a recipe and conduct an organoleptic evaluation of a dessert based on zucchini, apples and currants. The task was to conduct an organoleptic evaluation of the prototype sorbet. The study of organoleptic indicators was carried out in accordance with GOST 31986-2012 «Catering services. Method of organoleptic assessment of the quality of public catering products». Test batches of the dessert were carried out at the Volgograd State Agrarian University at the Department of Processing and Food Production Technologies. In terms of organoleptic indicators, the new product met all technical requirements. The appearance of sorbet, a single-layer dessert in the form of a ball without glaze, decorated with mint greens. The consistency was dense. The taste was clean, characteristic of apple and currant, without any foreign tastes or odors. The color was light green, uniform throughout the mass. The product sample met the requirements of GOST R 55624-2013 «Whipped frozen fruit, vegetable and fruit-vegetable desserts. Technical conditions». A tasting evaluation of the sorbet was carried out. Employing the arithmetic mean value, the overall rating of the prototype was the highest. The use of zucchini, green apple and white currant in combination in the production of sorbet has not reduced the quality criteria of this dessert.